Determination of the reference value for intra ocular pressure (IOP) in the Caspian miniature horse - Roushanak Sarkhoosh; saeed ozmaie; Ahmad Asghari; Alireza Jahandideh (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2020)
Assessing the intraocular pressure is a key parameter for eye examinations used to diagnose diseases of this organ of the body. Determining the IOP requires a tool that is fast, accurate, portable, and functional. Currently, there are accepted methods for determining IOP, which include rebound tonometry and the Applentation method. This study aimed to determine the reference value for intraocular pressure by using rebound tonometry in the Caspian horse. In this regard, 20 apparently healthy Caspian miniature horses, both male and female aged between 2 and 14 years old and weighing between 150 and 200 kg were selected. The total mean and standard deviation of the results obtained from the study of intraocular pressure in 20 Caspian miniature horses were calculated as 32.9±6.7 mm/Hg. Gender had no significant effect on IOP (p < /em>>0.05). No significant differences were seen between the mean IOP values of the left eye compared to the right eye. Given the importance of early diagnosis of glaucoma and the prevention of subsequent disorders, it seems that the obtained results could be used as reference to measure the intraocular pressure of Caspian miniature horses.